Introduction to Impacting Education Themed Issue: Voices from CANDEL: Leading for Equity and the Scholar-Practitioner Journey - Rodriguez, Rosaisela; Montaño, Elizabeth (Impacting Education: Journal on Transforming Professional Practice, 2024)
Educational leadership doctoral granting programs have been on the rise for the last 25 years. These programs recruit students who work full-time as educational leaders while completing full-time doctoral coursework. Previous research on educational doctoral programs has found that they provide unique access to doctorates in education (EdD) for first generation students and students of color. In addition to access, educational doctoral programs create spaces for these students to improve their leadership skills. This issue leverages and shares the voices of alumni of an educational leadership doctoral program and faculty. This special issue highlights what they have learned from their scholar-practitioner journeys. We organized the contributions into three themes that make visible the leadership and scholar-practitioner journeys of our alums and faculty. Most importantly, our contributors emphasize how their doctorate degrees have impacted their capacity for research to inform their everyday practice, and how their leadership abilities were enhanced by the transformative experiences they had in their program.